(untitled) (World Economics and Finance Bulletin, 2022)
The success of a culinary business cannot be separated from the presence of a brand that is able to make consumers have awareness of the brand in the hope that consumers will have an interest in purchasing. The purpose of this study was to determine the effect of brand awareness on the buying interest of consumers of Roti Ketawa Waka Waka. The number of respondents obtained by 92 people and carried out by testing the validity of the instrument it was found that the data had valid criteria and the reliability test had reliable criteria. For the normality test that the data has a normal distribution and the ability of brand awareness to explain buying interest is 43% with a strong correlation, the results of the simple regression equation show a positive direction coefficient of brand awareness on buying interest. The results of the hypothesis show that brand awareness has a positive and significant effect on buying interest, the stronger the ability of brand awareness for consumers, the buying interest from consumers will also be stronger.